A hospital-based study on long-term mortality and predictive factors after spontaneous intracerebral hemorrhage from Turkey - (:unkn) unknown (ASEAN NEUROLOGICAL ASSOC, 2009)
Background: There is no previous study on long-term mortality following spontaneous intracerebral hemorrhage in Turkey. The aim of this study is to investigate long-term mortality following spontaneous intracerebral hemorrhage and the predictive factors for mortality in hospitalized patients in a medical centre in Turkey. Methods: We retrospectively reviewed the hospital records of patients aged 18 and above, hospitalized with spontaneous intracerebral hemorrhage between January 2004 and March 2005, in the Dr. Lutfi Kirdar Kartal Training and Research Hospital, Istanbul. Demographic data, vascular risk factors, Glasgow Coma Scale score and neuroimaging findings were abstracted. Anamnestic findings consisted of the history of hypertension, diabetes mellitus, acetyl salicylic acid-warfarin use and family history of stroke. The anatomic localization, volume, and intraventricular extension of hematoma were determined on CT images. The patients or their family members were called up to determine 30-day and one-year mortality rates. Results: Thirty-day mortality was 38.3% and one-year mortality was 49.6%. The predictive factors for mortality Glasgow Coma Scale score on admission, blood glucose, hematoma volume and intraventricular extension of hematoma. Thirty-day mortality and one-year mortality did not differ with sex (p>0.05). All patients who have hematoma volume of over 60 cm(3) died within 30 days. There were correlation between hematoma volume and both 30-day and one-year mortality rates (p<0.001). The patients who had hematoma with extension to ventricles had significantly higher 30-day and one-year mortality rates (p<0.001). Conclusions: Mortality rate after spontaneous intracerebral hemorrhage was high as in other studies from elsewhere. Low level of consciousness on admission and high volume of hematoma were predictive of poor prognosis.
Keywords: POPULATION; AMERICANS; SURVIVAL